The Behavior of Institutional Investors on The Croatian Financial Market: A Study at The Zagreb Stock Exchange - Dina KORENT; Vlatka KOLEMBUS (Communications of International Proceedings, 2022)
The purpose of the paper is to identify, present and evaluate the behavior of institutional investors on the Croatian financial market. Specifically, the intention is to detect whether institutional investors on the Croatian financial market act dominantly according to the traditional approach, whether the influence of behavioral factors on investment decisions prevails, or whether the practices are equally divided between the aforementioned approaches. In addition to general scientific methods, especially in the empirical part, methods of descriptive statistics are used. Scientific and professional literature of the field, as well as primary data collected through a questionnaire, were used in the preparation of the paper. The research results suggest that the behavioral practices of institutional investors on the Croatian financial market are divided with the predominant influence of behavioral factors. Thus, institutional investors on the Croatian financial market are predominantly behaviorists who respect and apply certain concepts of the traditional approach. Considering, on the one hand, the shortcomings of the traditional approach that are manifested in real-world conditions and, on the other hand, criticisms of behavioral biases, the combination of the mechanisms of the traditional and behavioral approaches with a moderate dominance of the latter can be conditionally characterized as suitable. Conditional suitability implies and suggests to institutional investors on the Croatian financial market respect for the settings of the traditional approach and their behavioral adaptation to the conditions of the real world, with awareness and amortization of behavioral biases and their influence on investment decisions.
Keywords: behavior; institutional investors; financial markets; Republic of Croatia